"Doctors Killed My Baby": Argumentative Patterns in Medical Disputes in China. Issue 10 (3rd October 2018) - Pan, Dawei
ABSTRACT: The recent surge in medical disputes requires that more attention be paid to the voices of laypeople. This article explores the argumentative nature of the public discourse of the reported "malpractice mobs" that strive to convince members of the public (in the place of health or legal experts) that they have been victims of medical errors and injustice. This case-based qualitative empirical study uses a pragma-dialectical approach to suggest a prototypical pattern of such public appeals that contains a basic argumentative pattern and various types of extensions. The presence and influence of cultural factors are identified and discussed. The results of the analysis indicate that "malpractice mobs" largely display a tendency to target certain drugs, treatments or therapeutic methods based on folk interpretations of medical phenomena among individual ethnic groups, which may be regarded as cultural preferences in the medical domain. Although these preferences have little coercive power, in the absence of institutional restraints, they may have a powerful impact. The introduction of cultural preferences into pragmatic argumentation explains not only why some critical questions are emphasized (whereas others are invariably ignored) but also why certain types of support are repeatedly demanded in public appeals. The findings suggest the importance of paying greater attention to the argumentation of laypeople in medical disputes in China and the essential role of a culturally sensitive model of argumentation theory in improving health communication.